Progress towards improving homing and engraftment of hematopoietic stem cells for clinical transplantation. Issue 4 (July 2019) - Huang, Xinxin; Broxmeyer, Hal E.
Abstract : Purpose of review: Hematopoietic cell transplantation (HCT) is a life-saving treatment for a variety of hematological and nonhematological disorders. Successful clinical outcomes after transplantation rely on adequate hematopoietic stem cell (HSC) numbers, and the homing and subsequent short-term and long-term engraftment of these cells in the bone marrow. Enhancing the homing capability of HSCs has the potential for high impact on improving HCT and patient survival. Recent findings: There are a number of ways to enhance HSC engraftment. Neutralizing negative epigenetic regulation by histone deacetylase 5 (HDAC5) increases surface CXCR4 expression and promotes human HSC homing and engraftment in immune-deficient NSG (NOD.Cg-Prkdc scid IL2rgt m1Wjl /Sz) mice. Short-term treatment of cells with glucocorticoids, pharmacological stabilization of hypoxia-inducible factor (HIF)-1α, increasing membrane lipid raft aggregation, and inhibition of dipeptidyl peptidase 4 (DPP4) facilitates HSC homing and engraftment. Added to these procedures, modulating the mitochondria permeability transition pore (MPTP) to mitigate ambient air-induced extra physiological oxygen stress/shock (EPHOSS) by hypoxic harvest and processing, or using cyclosporine A during air collection increases functional HSC numbers and improves HSC engraftment. Summary: A better understanding of the regulation of human HSC homing mediated by various signaling pathways will facilitate development of more efficient means to enhance HCT efficacy.